2017
DOI: 10.1016/j.nanoen.2016.12.017
|View full text |Cite
|
Sign up to set email alerts
|

3D Hierarchical nano-flake/micro-flower iron fluoride with hydration water induced tunnels for secondary lithium battery cathodes

Abstract: As a potential multi-electron electrode material for next generation lithium ion batteries, iron fluoride (FeF 3 ) and its analogues are attracting much more attentions. Their microstructures are the key to achieve good electrochemical performances. In this work, FeF 3 ·3H 2 O nano-flakes precursor with high crystallinity and flower-like morphology is synthesized successfully, by a liquid precipitation method using Fe(NO 3 ) 3 ·9H 2 O and NH 4 HF 2 as raw materials. The formation and the crystal growth mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
55
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(62 citation statements)
references
References 57 publications
0
55
0
Order By: Relevance
“…Therefore, the efficient storage of energy is also a severe challenge. [7] Transition metal fluorides as conversion-type cathode materials are regarded as the most promising candidate for the next generation of cathodes. So, it is widely used for portable handheld devices, electric vehicle and other large-scale application systems, etc.. [1,3] However, the low specific capacities of traditional intercalated electrode materials cannot be satisfied the eager demand of high capacity.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the efficient storage of energy is also a severe challenge. [7] Transition metal fluorides as conversion-type cathode materials are regarded as the most promising candidate for the next generation of cathodes. So, it is widely used for portable handheld devices, electric vehicle and other large-scale application systems, etc.. [1,3] However, the low specific capacities of traditional intercalated electrode materials cannot be satisfied the eager demand of high capacity.…”
Section: Introductionmentioning
confidence: 99%
“…[5,8] Among them, iron fluoride (FeF 3 ) has been widely studied because the high theoretical capacity of 712 mAh g À 1 (delivering three electrons) and working potential (about 3.0 V for the redox reaction). Researchers have made great efforts to overcome these defects, such as morphology and structure regulation, [7,[14][15][16][17] nano-refinement, [7,14,18,19] developing derivatives of FeF 3 , [6,[20][21][22] doping metal atoms [22][23][24] and combining FeF 3 nanoparticles with conductive materials. [10][11][12] However, the strong ionic character of FeÀ F bonds lead to poor electronic conductivity and inferior kinetics, which greatly limits the capacity for storing lithium.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many research groups reported in the 1990s a small reversible capacity of 80 mAh g −1 for FeF 3 . The electrochemical reaction of the conversion mechanism was shown by these groups to be very rate and temperature sensitive [7][8][9]. This is due to the structural decomposition and reconstruction of the metal fluoride as well as the transport of the lithium ions in the bulk phase.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Among the various SIBs cathode materials, iron-based fluorides, such as FeF 3 , FeF 3 · 0.5H 2 O, Fe 2 F 5 · H 2 O and FeF 3 · 0.33H 2 O, have caused tremendous interest due to high operational voltage (average ∼2.74 V vs. Na/Na + ), nontoxicity and low-cost. 8 Especially, in the family of iron-based fluorides, the nanoscale FeF 3 · 0.33H 2 O has a great prospect because its unique tunnel structure and high theoretical specific capacity. The tunnel structure is beneficial to electrolyte ion penetration, Na + transport, and interfacial processes.…”
mentioning
confidence: 99%